Multiplex autoantibody screening in pediatric type 1 diabetes: POC Blot vs. ELISA for gluten-related disorders - Negussie, Adugna; Wusterhausen, Patricia; Muleta, Deselegn; Mulugeta, Demise; Bekele, Mesfin; Matthias, Torsten (Frontiers in Immunology, 2026)
BackgroundType 1 diabetes (T1D) is frequently associated with various autoimmune disorders, including gluten-related disorders (GRDs). Early screening for autoantibodies can provide insights into the co-occurrence of these conditions in pediatric patients. This study aims to evaluate the performance of a Point-of-Care Test (POC) BLOT based assay in comparison to the conventional enzyme-linked immunosorbent assay (ELISA) for multiplex autoantibody screening for gluten-related disorders in children with T1D.MethodsA cohort of pediatric and adolescent patients diagnosed with T1D was recruited for the study. Both POC-BLOT and ELISA methods were utilized to screen specific autoantibodies associated with GRDs, including anti-gliadin and anti-transglutaminase antibodies. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated for both screening methods. Statistical analyses were conducted to compare the results of the two assays.ResultsA total of 192 participants were included in the study. The overall method agreement between the POC-BLOT and the ELISA test was approximately 90%. The PPV and NPV for both methods were also calculated indicating that the performance of the POC assay was comparable to ELISA. Additionally, results indicated that the POC assay provided faster results, highlighting its potential utility in clinical pediatric settings.ConclusionThe POC blot assay demonstrates promising potential as a reliable and rapid screening tool for autoantibodies in pediatric patients with T1D and gluten-related disorders in resource-limited settings. While further validation is needed, these findings suggest that POC testing could facilitate earlier diagnosis and improve the clinical management of coexisting autoimmune conditions in this population.